Impulsiveness in Online Era: The Role of Utilitarian and Hedonic Value on Impulsiveness and Impulse Buying Behavior of Batam Community - Fendy Cuandra (Politeknik Negeri Bengkalis, 2022)
This study aims to analyze the impulse buying behavior of the Batam City community by examining Utilitarian and Hedonic values that arise due to browsing and online reviews, as well as the influence of a person's impulsiveness. This study used a questionnaire as an instrument of research data collection which obtained 158 research samples who were residents of Batam City. Furthermore, the data is processed and analyzed using the SmartPLS 3.0 program. The results of testing and processing research data identify the influence of impulsiveness and hedonic values on impulse buying behavior, the effect of hedonic values on browsing, and the impact of mediation by browsing on the indirect relationship between hedonic values and impulse buying behaviors. But the results of this study also show a different outcome, namely where utilitarian values do not affect browsing and impulse buying behavior of Batam Community, as well as browsing which shows no mediation impact on the relationship.